2018
DOI: 10.1002/ece3.4299
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of chemical defenses along invasion routes: Harmonia axyridis Pallas (Coccinellidae: Coleoptera) as a case study

Abstract: The evolution of increased competitive ability (EICA) hypothesis (Blossey & Nötzold, 1995) postulates that escaping from coevolved enemies increases invaders fitness by energy reallocation from defenses and immunity to growth and reproduction. In this context, we evaluated the evidence of evolutionary change in invasive populations of Harmonia axyridis Pallas (Coccinellidae: Coleoptera). We measured egg defenses—cocktail of hydrocarbons on the egg's surface flagging egg toxicity and the concentration of the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Additionally, as time progresses, not only do consumers become less wary of invaders and change their foraging behaviour as described here, but other mechanisms could also influence in strengthening the biotic interactions. For instance, over time, invaders may also undergo physiological changes that could reduce either their toxicity or their allelochemical potential (Lankau et al, 2009 ; Magro et al, 2018 ; Van Kleunen et al, 2018 ), thus becoming more susceptible to biological control by competition or herbivory. For this reason, snapshot studies that only focus on a specific point in time give us only a limited view of the importance of biotic resistance towards an invader since the outcomes may vary greatly influenced across time.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, as time progresses, not only do consumers become less wary of invaders and change their foraging behaviour as described here, but other mechanisms could also influence in strengthening the biotic interactions. For instance, over time, invaders may also undergo physiological changes that could reduce either their toxicity or their allelochemical potential (Lankau et al, 2009 ; Magro et al, 2018 ; Van Kleunen et al, 2018 ), thus becoming more susceptible to biological control by competition or herbivory. For this reason, snapshot studies that only focus on a specific point in time give us only a limited view of the importance of biotic resistance towards an invader since the outcomes may vary greatly influenced across time.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, resources invested in defense are traded off against growth and reproduction in plants (Herms & Mattson, 1992 ) and in animals (Braendle et al, 2011 ). For BCAs, Magro et al ( 2018 ) reported evolutionary changes leading to an increase in reproduction and a decrease in defense for three populations of the ladybird H. axyridis along its invasion route (Figure 1 ). This and other studies also show that, at length, natural enemies in the introduced range might adapt to the exotic BCA leading to a shift in selection toward better defended genotypes with negative consequences for competition capacities (Knapp et al, 2019 ), which could eventually limit the BCA success in biological control programs.…”
Section: Natural Processes Of Evolution and Biological Controlmentioning
confidence: 99%